Different pathways and biomarkers of acute and chronic cyclosporineinduced nephrotoxicity in a rat model: focus on overexpression of mTOR and Mki67 - Sereno,Jose (2013)
Calcineurin inhibitors, in particular Cyclosporin A (CsA), remains the cornerstones of immunosuppressive regimens in many transplantation centres worldwide, regardless of drug-induced nephrotoxicity. The pathogenesis of CsA-induced nephropathy remains to be fully elucidated, but seems to be affected by the duration of drug exposure. This study aimed to clarify the molecular pathways involved in acute and chronic CsA-induced nephrotoxicity, focusing on serum, urinary and renal markers. The study comprised 24 male Wistar rats, divided in two models: acute and chronic CsA (5 mg/Kg bw/day) exposure (3 vs 9 weeks) vs matched control groups. The following data was evaluated: blood pressure and heart rate; serum total and non-HDL cholesterol, glucose and insulin; serum and urine creatinine, blood urea nitrogen (BUN), clearances and glomerular filtration rate (GFR); serum, urine and kidney tissue lipid peroxidation, via malondialdehyde (MDA); kidney mRNA expression of proliferative markers (PCNA, TGF-β1, mTOR and Mki67); kidney lesions. CsA has promoted hypertension and tachycardia, which were aggravated with the duration of exposure. Creatinine and BUN clearance and GFR showed early renal dysfunction, accompanied by increase serum creatinine (p<0.05) and BUN (p<0.01) levels, as well as kidney lipid peroxidation (p<0.05), which worsened with chronic exposure. Renal lesions were evident only after the chronic treatment. However, acute CsA exposure induced PCNA and TGF- β1 kidney mRNA up-regulation (p<0.05), unchanged mTOR and down-regulation of Mki67, while chronic treatment revealed a normalized PCNA and TGF- β 1 expression, accompanied by prominent mTOR and Mki67 up-regulation (p<0.01). In conclusion, CsA-induced nephrotoxicity is aggravated over time and distinct mechanisms and markers are involved in acute and chronic exposure. Chronic nephrotoxicity is accompanied with intense overexpression of mTOR and Mki67. These findings reinforce the rationale for early substitution of CsA by less nephrotoxic agents, being mTOR inhibitors a validated choice, in order to prevent chronic CsAinduced nephrotoxicity